Renal Failure in Diyala Province - Fathalla Askar, Haneen; M Athab, Ahmed; A Shakir , Shahab; K Mohamad Ali, Nabeel (Diyala Journal of Medicine, 2019)
Background: Renal failure is a worldwide health problem. The incidence and prevalence of renal failure is in constant increase, involving poor outcomes and high costs. The major leading causes of kidney failure are type 2 diabetes and hypertension. Objective: To study the epidemiology of renal failure in diyala province. Patients and Methods: A cross sectional study including a review of 284 cases of Renal Failure recorded in Ibn Sina dialysis center in Baqubah teaching hospital in Diyala province for the period from 1st January to the 31st of December of 2018. The collected data was analyzed by using computer, excel and using of SPSS-24. All the variables were analyzed by number, proportion and percentage. Results: Renal failure prevalence rate was 189.2 PMP and Incidence rate was 112.6 PMP in Diyala province. The Prevalence was in AL-Khalis city 363.15 PMP, Baqubah city 246.9 PMP, Baladroz city 190.9 PMP, AL-Muqdadia city 134.7 PMP and Khanaqin city 100.96 PMP. The mean age of renal failure in Diyala province was 52.9±15.9 yrs. Males was about 60.5% and females was 39.4%. The reasons of Renal failure ratio was diabetes about 33.4%, Hypertension about 23.6%, Unknown cause about 27.4%, Glomerilonephritis about 5.3%, Obstructive nephropathy about 3.16%, Congenital about 2.8% and others about 4.22% . The major co-morbidities in renal failure patient on Hemodialysis was anemia about 48.94%, Hypertension about 35.2%, Heart failure about 4.57%, Ischemic heart disease about 10.56% and Cerebrovascular accident about 0.7%. Withdrawal from hemodialysis program in 2018 was 47.3%. Conclusion:The incidence rate was high and the prevalence rate was low due to low survival. DOI:https://doi.org/10.26505/DJM.17024600409